A study about the role of the human factor in maritime cybersecurity - Thanasis Pseftelis; Gregory Chondrokoukis (SPOUDAI - Journal of Economics and Business, 2021)
Shipping is the sector of the economy via which approximately 85% of all world trade is transported and which is technologically developing with enormous leaps. Its digital transformation has highlighted new opportunities, but at the same time new threats. Due to the great demand from the maritime community for digital operations (specifically digitization and automation), maritime cyber security is becoming an issue of utmost importance. A protection framework through which shipping can be shielded against cyber-threats is absolutely necessary. As hackers are becoming increasingly aware of cyber-vulnerabilities within the maritime sector and shipping is undoubtedly a key pillar of the Greek economy, this study fills the existing gap by presenting a survey carried out within the Greek maritime community with the aim to investigate the human factors and the awareness stakeholders have about maritime cybersecurity. Our detailed research resulted in two main findings. Firstly, it was found that the basic principles of security (availability, integrity, confidentiality) and the related information and communication technologies (ICT) have not been adequately understood in order to be protected from cyberattacks. Secondly, our perception that the human factor can contribute to maritime cybersecurity in a positive or negative way was confirmed.
Keywords: L86; L92; 330; Cybersecurity; human factor; maritime; empirical research